CONCEPTUAL AND THEORETICAL ISSUES INVOLVED IN THE MIGRANTS OF KERALA - SHYLA HAMEED
There are both economic and social imbalances among states in India and this leads to internal migration in general. High literacy rates, better education and lack of professional and skilled jobs had prompted Keralites to look for higher wages and skilled labour outside India. This trend has led to a decline in the availability of workforce in Kerala especially in unskilled jobs. Kerala has the lowest population growth rate in the country and is set to become the first state with zero population growth rates or with a negative growth rate. The structure of Kerala economy has change from one dominated by agriculture to one dominated by services sector. This is primarily due to growth of both public and private services necessitated by increased demand due to the high remittances from abroad. The manufacturing sector is no longer attractive to the entrepreneurial class in Kerala and much investment has taken its course to the service sector which is not governed by strict labour laws. The State does not produce many things it should have and nature and quantity of labour demanded and supplied. For instance there is labour shortage for traditional agriculture purposes or for manual work as well as for trained and skilled personnel in emerging areas of employment. Due to this acute shortage of manpower, in the farm and construction sector over the recent years, has encouraged migration of casual workers from other states of India. Migration in general, internal or inter-state, migration of labour is an age-old phenomenon in India. The people compelled to migrant due to two factors-development; driven factors and distress factors. On one hand, the migration of people is mainly motivated by the desire to access better employment opportunities, higher wages, good quality education, health condition and better living conditions. While on the other hand, it is also impelled by push or distress factors at home such as the lack of employment, low wage rates, agriculture failure, debt, drought and natural calamities. Both these reasons are equally responsible for migration of casual workers to Kerala has thus lost reasonably stable and secure jobs which come from the manufacturing sector. Consequently there has occurred a structural imbalance in the labour market of Kerala.